BELIEF AS A METHOD OF THE SPIRITUAL AND MORAL EDUCATION IN CLASSES 3 PHYSICAL CULTURE (Pedagogy of Higher and Secondary Education, 2007)
The article reveals persuasion as a method of spiritual and moral upbringing in the educational process of higher school.